2018
DOI: 10.1021/acs.iecr.8b01941
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Methyl Methacrylate Grafting on Model Single Fatty Acid Alkyds

Abstract: Four model alkyds were prepared by the fatty acid process using a single fatty acid (stearic, oleic, linoleic, or linolenic acid) with phthalic anhydride and glycerol. These model alkyds were reacted with methyl methacrylate (MMA) in the presence of benzoyl peroxide or azobis(isobutyronitrile). 1 H NMR, 2D gradient heteronuclear multiple quantum coherence NMR, matrix assisted laser desorption ionization mass spectrometry, solvent extraction, and gas chromatography were used to evaluate each model alkyd system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Thereby, fatty acids, polyols and polyacids are added together and react through esterification reaction (Scheme 4). 4,8,34 Scheme 4: Polymerization of alkyd resin using fatty acids…”
Section: Scheme 3: Acidolysis Reaction To Modify Triglyceride Oil Witmentioning
confidence: 99%
“…Thereby, fatty acids, polyols and polyacids are added together and react through esterification reaction (Scheme 4). 4,8,34 Scheme 4: Polymerization of alkyd resin using fatty acids…”
Section: Scheme 3: Acidolysis Reaction To Modify Triglyceride Oil Witmentioning
confidence: 99%
“…The reactivity of different unsaturated fatty acids and TOFA based materials in grafting reactions, for example, with acrylic monomers has been studied, when so-called alkyd-acrylic copolymers and hybrid material have been prepared. It has been shown that both the isolated double bonds of oleic acid and the double allylic sites of linoleic and linolenic acids are reactive in free radical grafting reactions with monomers such as methyl methacrylate or butyl acrylate (Uschanov et al 2008;Wang et al 2018).…”
Section: Treatment Of Cellulose Fibres With Tofa Lignin Nanoparticlesmentioning
confidence: 99%
“…The TOFA and fatty acid esters of lignin have been synthetized to produce novel lignin-based products, for example, for coating of paper boards and to improve board properties (Hult et al 2013), or to improve compatibility of lignin with polystyrene (Pawar et al 2016). TOFA compounds contain reactive double bonds that can be utilized for grafting purposes (Uschanov et al 2008;Rämänen and Maunu 2014;Wang et al 2018). Lignin esters of maleic acid or trans-2-butenoic acid (crotonate) derivatives have also been used for improving the reactivity of lignin towards cross-linking and grafting reactions in thermal processes (Hu et al 2014;Luo et al 2018).…”
Section: Introductionmentioning
confidence: 99%